2022
DOI: 10.1108/ohi-08-2022-0214
|View full text |Cite
|
Sign up to set email alerts
|

Mosque as a multi-functional public space destination: potential breathing space in dense urban fabrics of Hail City, Saudi Arabia

Abstract: PurposeThe general concept of public space in Saudi Arabia is relatively recent; it is the result of an attempt to modernize several conservative traditions and norms, as well as the ambitious vision of 2030, which reprioritized Saudi cities' public spaces by implementing a quality-of-life improvement program. This study aims to investigate the relationship between mosque location and surrounding urban context as a significant urban design issue in order to comprehend the potential for transforming such an ele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 19 publications
(25 reference statements)
0
2
0
Order By: Relevance
“…The data analysis revealed that the circular mosque prototype has three main areas with shortcomings: planning failure, design failure and implementation and construction failure. First and foremost, a mosque should serve as a symbolic and active public space for the community (Alnaim and Noaime, 2022). However, it is evident from Figures 3 and 4-A, 4-C that the circular prototype does not integrate well with the surrounding urban context.…”
Section: Discussion and Findingsmentioning
confidence: 99%
“…The data analysis revealed that the circular mosque prototype has three main areas with shortcomings: planning failure, design failure and implementation and construction failure. First and foremost, a mosque should serve as a symbolic and active public space for the community (Alnaim and Noaime, 2022). However, it is evident from Figures 3 and 4-A, 4-C that the circular prototype does not integrate well with the surrounding urban context.…”
Section: Discussion and Findingsmentioning
confidence: 99%
“…(4) Focus on comprehensiveness: Ecological art and socially engaged design emphasize comprehensiveness, signifying that design considerations extend beyond individual public spaces to encompass the entire city and other relevant factors. Therefore, in the process of public space transformation, it is necessary to initiate from city-wide planning and actual circumstances, incorporate multiple interests, coordinate various resources, and develop different transformation plans based on different spatial areas, achieving overall harmony in the public spaces [3].…”
Section: Principles Of Integrating Eco-art and Socially Participatory...mentioning
confidence: 99%
“…Consequently, we have observed the proliferation of central mosques across Ghana, but a persistent dearth of individuals capable of effectively administering these religious institutions remains. According to Allia et al (2013), effective management of the mosque plays a crucial role in ensuring the successful provision of services to the public (Alnaim and Noaime, 2023). Hence, it is imperative for a mosque to have efficient and meticulously structured management strategies.…”
Section: Problems Associated With Estate Management Practices For Mos...mentioning
confidence: 99%